2020
DOI: 10.1080/0167482x.2020.1857360
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review involving 11,187 participants evaluating the impact of COVID-19 on anxiety and depression in pregnant women

Abstract: Background: COVID-19 has started to spread within China since the end of December 2019. As a special population, the pregnant and delivery women maybe influenced both in physical and psychological aspects. The meta-analysis was conducted about mental health in pregnant and delivery women. Methods: We searched both MEDLINE, EMBASE, Cochrane Library in English and CBM, CNKI, WANFANG and CSSCI in Chinese to find literature from December 2019 to 31 July 2020 related to COVID-19 and mental health in patient with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 49 publications
6
78
3
4
Order By: Relevance
“…The heterogeneity of study designs and inconsistent results clearly indicate the need for summative research-namely reviews, which contribute to delineate the impact of the pandemic on the mental state of pregnant women and new mothers. Previous systematic reviews [16,17,19,20] and a recent rapid review [18] have focused on the prevalence of anxiety and depression among pregnant women and new mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity of study designs and inconsistent results clearly indicate the need for summative research-namely reviews, which contribute to delineate the impact of the pandemic on the mental state of pregnant women and new mothers. Previous systematic reviews [16,17,19,20] and a recent rapid review [18] have focused on the prevalence of anxiety and depression among pregnant women and new mothers.…”
Section: Discussionmentioning
confidence: 99%
“…A few systematic reviews with meta-analysis following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [15] have been carried out. The results of the reviews concerning antenatal psychological symptoms indicate increased severity of anxiety [16] and increased prevalence of anxiety and depression [17][18][19] in pregnant women during the COVID-19 pandemic. Based on a systematic review with meta-analysis, Yan et al [20] found high rates of anxiety, depression and insomnia in pregnant women and new mothers.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review by Sun et al [10] showed an overall prevalence of 30% for depression and 34% for anxiety. When specifically looking at depression rates, it ranges from 11-65% between studies and subgroup analyses showed a large difference in relation to different assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted regarding the mental health of pregnant women during COVID-19. Sun et al [10] conducted a systematic review including 15 studies about pregnant women that were performed during the first wave of the pandemic. The results showed an overall prevalence of 30% (range 11-65%) for depression and 34% (range 18-56%) for anxiety, although significant heterogeneity was seen.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of 2019, the novel coronavirus disease (COVID-19) appeared and caused global concern. It is a highly infectious disease characterized by respiratory symptoms [1] . COVID-19 pandemic has caused an unprecedented and uncontrollable health crisis.…”
Section: Introductionmentioning
confidence: 99%